The effect of exercises for the mobile force in the circular style in the development of compound offensive skills and the effectiveness of basketball performance - عمر هلال عبد الكريم Gomaa Mohamed Awad, (Mustansiriyah Journal of Sports Science, 2024)
The importance of research in finding special exercises and a specific style that suits the need for organization that ensures the legalization of training and its organization to ensure accurate physical and technical performance according to the physical load appropriate to the nature of the technical and this method is the circular method, and the research problem was identified in a noticeable and continuous decline for several consecutive seasons that expresses a low level of effectiveness of a player Basketball, and the objectives of the research were determined in ensuring the impact of exercises used in the development of the mobile power of the muscles of the legs and offensive skills compound basketball and the effectiveness of performance, the research sample is a group of basketball players aged under 18 years selected in a deliberate way and the researcher used the appropriate tests for his research and then reached several conclusions after the implementation of his field experiment, the most important of which is that all variables of the study have evolved positively and that the moving force is important The style of circular training had a positive impact on the organization and legalization of training.